What brings youth to recreational parks? - Zainol, R.; Au-Yong, C.P. (Malaysian Institute of Planners, 2016)
Locations of recreational parks are said to have a direct influence on youth physical activities. However, there is still a lack of studies on youth activities at recreational parks. Thus, this study examines the relationship between reasons and habit of youth going to recreational parks through a questionnaire survey. Variables that are measured include enjoying the outdoors, use a particular facility at the park, play sports, picnic and general activities, walk or ride a bicycle for exercise and meeting friends. Logistic regression analysis reveals youths are most likely to visit the park for playing sports, walking or riding a bicycle, provided the facilities and amenities are available. Hence, planning, implementation and maintenance of recreational park play a significant role in promoting outdoor activities and active lifestyle among the youth.